Determination of the trape depth of (ZnS) 1-x (MnTe)X Using theromoluminescence. - Pateriya, Deepti; Baghel, R N; Besen, D P; Chandr, B P (Recent Research in Science and Technology, 2012)
Thermoluminescence (TL) is a thermally stimulated light emission following the removal of excitation from an insulator or semiconductor. For luminescence emission,excitation is provided by irradiating the sample with X-ray or other ionizing radiation like α,β and ÎŽ –ray. It should be noted that once heated to excite the light emission, the material can not be made to emit the thermoluminescence again by simply cooling the specimen and reheating.